A Framework for Hospital Characterization - Parsia, Yasaman; Puteri Fadzline, Muhamad Tamyez; Sorooshian, Shahryar (Medwell Journals, 2017)
One of the important factors of each society is health. Providing health-care services should be at the first level of society plans in each country. It is important to pay huge attention to build suitable structure for hospital developments. Modem hospitals may have variety units and departments, for instance, outpatient, inpatient, medical and supporting departments. Moreover, each of the departments maybe has some sub-departments. Therefore, it is important to present a framework to characterize hospitals for deeper understanding of such a modem healthcare centre requirements as it is attempted in this technical note.